Portraying EFL teacher's questioning strategies and practices: the case of a vocational school in Indonesia - Nurti Rahayu; Dwi Sloria Suharti (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2023)
Although many studies have explored teacher questioning strategies (TQS) in EFL classrooms, only some studies have been conducted in EFL online classes in a vocational high school context. This study aims to shed the EFL online classroom practices regarding using first language and teacher's questioning strategy. To this end, a qualitative case study was conducted at one public vocational school in Karawang, West Java, Indonesia. Data were collected through Zoom recordings for four sessions and classroom observation. Additionally, follow-up interviews were conducted after the classes. The data were analysed with thematic analysis. The findings revealed bilingual classrooms with teachers adopting the first language to build rapport, ice-breaking, and grammar explanation. The teachers also adopted various TQS: rephrasing, repetition, simplification, and decomposition. The findings confirm the roles of teachers' questioning strategies to improve students' engagement. This engagement contributes to students' understanding, resulting in enhanced learning effectiveness. Therefore, teachers need to strengthen their awareness of their questioning abilities to optimise the teaching and learning experience in the classroom.